Housing Market Dynamics in Africa - Bah, El-hadj M. (Springer Nature, 2018)
Housing finance; Slum upgrading; Africa; Construction; Political economy; Land tenure; Housing development; Urban planning; Real estate; Public policy; Property rights; Economics